Improvement of Cycling Capability of Li2S-FeS Composite Positive Electrode Materials by Surface Coating With Titanium Oxide - Yamauchi, Erina; Takeuchi, Tomonari; Sakaebe, Hikari (Frontiers in Energy Research, 2019)
High-energy-density batteries are actively sought after for next-generation electric vehicle (EV) applications, triggering the search for sulfur-based positive electrode materials with high capacity for extended driving range. One of the primary issues of sulfur cathodes is the rapid capacity decay caused by the dissolution of sulfur in the electrolyte and the resulting parasitic reactions. This can be prevented by incorporating a suitable amount of carbon material into the sulfur electrodes, because of its inherent properties; however, introducing a large amount of low-density carbon materials will lead to a decrease in the energy density of the battery. Therefore, an alternative method to suppress sulfur dissolution is required for commercial applications. Recently, we developed a Fe-containing Li2S-based material (Li8FeS5) as the sulfur cathode; it has a relatively high initial discharge capacity (>700 mAh·g−1) and electric conductivity. However, rapid capacity degradation was observed during the initial several cycles, due to some unknown reactions between the electrolyte and Li8FeS5. In this study we demonstrate an effective method to improve the cycle performance of Li8FeS5 by coating its surface with a stabilizing material. We selected titanium oxide as the coating material, based on its high stability toward liquid electrolytes and its strong interaction with sulfur. Hence, we obtained TiOx-coated Li8FeS5 particles (Li8FeS5-TiOx) by a liquid-phase reaction. The transmission electron microscopy observation revealed that the Li8FeS5 particles were coated with several tens of nanometers of TiOx layers. The Li8FeS5-TiOx cells exhibited improved cycling performance with a carbonate electrolyte. We also observed that the capacity originating from an iron redox was not affected by coating during the cycling test; in contrast, the degradation of the cell capacity corresponding to the sulfur redox was suppressed significantly after coating with the TiOx layer. Thus, the surface reaction of Li8FeS5 with the electrolyte, which could be the main reason for the cycling degradation, was effectively suppressed by coating with the TiOx layer.